The Ionospheric Effects of the 2022 Hunga Tonga Volcano Eruption and the Associated Impacts on GPS Precise Point Positioning Across the Australian Region - B. A. Carter; R. Pradipta; T. Dao; J. L. Currie; S. Choy; P. Wilkinson; P. Maher; R. Marshall; K. Harima; M. Le Huy; T. Nguyen Chien; T. Nguyen Ha; et al. (Space Weather)
Abstract The Hunga Tonga Volcano eruption launched a myriad of atmospheric waves that have been observed to travel around the world several times. These waves generated traveling ionospheric disturbances (TIDs) in the ionosphere, which are known to adversely impact radio applications such as Global Navigation Satellite Systems (GNSS). One such GNSS application is Precise Point Positioning (PPP), which can achieve cm‐level accuracy using a single receiver, following a typical convergence time of 30 min to 1 hr. A network of ionosondes located throughout the Australian region were used in combination with GNSS receivers to explore the impacts of the Hunga Tonga Volcano eruption on the ionosphere and what subsequent impacts they had on PPP. It is shown that PPP accuracy was not significantly impacted by the arrival of the TIDs and Spread‐F, provided that PPP convergence had already been achieved. However, when the PPP algorithm was initiated from a cold start either shortly before or after the TID arrivals, the convergence times were significantly longer. GNSS stations in northeastern Australia experienced increases in convergence time of more than 5 hr. Further analysis reveals increased convergence times to be caused by a super equatorial plasma bubble (EPB), the largest observed over Australia to date. The EPB structure was found to be ∼42 TECU deep and ∼300 km across, traveling eastwards at 30 m/s. The Hunga Tonga Volcano eruption serves as an excellent example of how ionospheric variability can impact real‐world applications and the challenges associated with modeling the ionosphere to support GNSS.